SISTEM PENILAIAN KINERJA KARYAWAN (Studi Kasus PT. JTEKT Indonesia Karawang - Jawa Barat) - Siswandi, Siswandi; Devi, Sri Ratna (JAB (Jurnal Akuntansi & Bisnis), 2018)
Research Objectives to find out and measure how employee performance appraisal systems at PT. JTEKT Karawang West Java The methodology of writing uses qualitative descriptive involving all employees of PT JTEKT Karawang West Java by using random sampling with proportional random sampling of 50 employees Data collection techniques through questionnaires in support the documentation method while the data analysis technique is based on the employee performance appraisal system in accordance with the standards set by the company, using future-oriented methods, namely self assessment and evaluation by superiors. The results of the employee performance assessment will be used as material consideration in determining bonuses and increasing levels / employeesÂ Keywords : Employees, Policy ,Performance and asessment